A Study on Understanding to What Extent Digital Marketing Influences Sales in Small Enterprises in India - Sethi, Tarina (Digital Repository of Theses - SSBM Geneva, 2025)
Visualizing a business without marketing seems unfeasible. Even before starting a business, one must conceive a marketing plan along with a business idea to effectively communicate their product to the world. Marketing is inevitable for the very existence of the business. Before spreading awareness in the target market about the product, an attempt has to be made to familiarize them with the name of the brand, which cannot be executed without marketing efforts. The switch from traditional marketing to a completely digitized process, along with artificial intelligence, has been one of the most radical changes experienced over the past decade. There are various businesses today that use digital marketing as a tool to attempt to reach target audiences, while some have solely established digital audiences as their target market. Businesses choose Digital marketing from various aspects based on their marketing needs. These include content marketing, email marketing, social media marketing, video marketing, search engine optimization, pay-per-click, and more. These might be used together to synergize the effects of marketing activities. The goal of undertaking this study was to observe and learn to what extent digital marketing influences sales in small enterprises. The research method that was undertaken for conducting out this study was exploratory. Three small enterprises in India were chosen to seek an in-depth understanding and insights into how digital marketing helped them influence sales, along with their understanding and usage of artificial intelligence (AI). Semi-structured interviews were conducted using a questionnaire as a broad guideline. The results showcased that all three small enterprises viewed digital marketing as an important tool for achieving marketing objectives. They adopted it even before officially launching their business. It particularly helped them in bringing leads for their business, but digital marketing did not have a direct impact on the conversion of these leads since it depended on more factors. Digital marketing surely brought them the desired awareness, credibility, and reach for their business.